Development of A Canva-Based Interactive E-Module in Arabic Language Learning on The Topic of Al-Sa'ah at MTsN 2 Sinjai - Nurhikmah Rahing; Hamka Ilyas; Azizul Hakim (Abjadia : International Journal of Education, 2026)
This research aims to analyze student’s needs for interactive e-module teaching materials based on Canva in the Arabic language subject focusing on the topic of al-sa’ah for Grade VIII at MTsN 2 Sinjai, describe the development procedures of Canva-based interactive e-module teaching materials, and assess the validity and practicality of these teaching materials. This study is a type of research and development (R&D) designed to produce Canva-based interactive e-modules. The research design employs the 4D model by Thiagarajan, Semmel, and Semmel, which includes the stages of define, design, develop, and disseminate. The results of the research and development consist of a needs analysis showing the demand for Canva-based interactive e-modules. The validity analysis of the developed e-module falls into the "highly valid" category, with a validity percentage of 93.75% from material expert and 96.16% from media expert. Furthermore, the practicality test results indicate that the Canva-based interactive e-module is rated "highly practical" by teachers and students, making it suitable for use in Arabic language learning on the topic of al-sa’ah for Grade VIII. This study has implications for the availability of digital teaching materials for the Arabic language subject, specifically on the topic of al-sa’ah for Grade VIII, which meets validity and practicality requirements. The e-module supports self-regulated learning by allowing students to control their learning pace and practice independently through interactive features. However, this study has some limitations, namely that it has not yet tested the long-term effectiveness of the e-module, leaving room for further research on the impact of this e-module on improving student learning outcomes.